Revisión de la versión adaptada del Cuestionario de Expectativas hacia el Alcohol (AEQ) para jóvenes universitarios - Martha Leticia Salazar Garza; Silvia Jazmín Ortiz Noriega; Ma. de los Ángeles Vacio Muro (Centros de Integración Juvenil A.C., 2018)
Introduction: the Alcohol Expectancy Questionnaire (AEQ) is used to measure the beliefs of individuals about alcohol consumption. In Mexico there is an adaptation of the instrument, although when reviewing it, it was concluded that some items did not reflect beliefs in terms of a causality relationship and that the response options presented in a dichotomous manner reduced the possibility that students respond in a way that is closer to your reality. Objective: obtain the psychometric characteristics of a revised and modified version of the AEQ, previously adapted in Mexico. Method: a sample of 510 university students, following the rules for the development and revision of instrumental studies; through the use of confirmatory factor analysis and concurrent validity analysis. Results: the final version of the instrument was composed of 26 items, in seven factors: disinhibition, self-confidence, tension reduction, relaxation, increased sexuality, social interaction and psychophysiological changes; with a general Reliability index of .937. Discussion and conclusions: possibly the conceptual and operational review influenced the re-arrangement and elimination of reagents in comparison with the previously adapted version in our country. However, the analyzes show that positive expectations have a positive relationship with the frequency of excessive alcohol consumption. A shorter version of the AEQ was obtained, with content validity, factorial and concurrent, and an acceptable reliability index for each dimension.----------------------- Introducción: el Cuestionario de Expectativas hacia el Alcohol (AEQ) es empleado para medir las creencias de los individuos sobre el consumo de esta sustancia. En México se cuenta con una adaptación del instrumento, aunque al revisarlo se llegó a la conclusión de que algunos ítems no reflejaban las creencias en términos de una relación de causalidad y que las opciones de respuesta presentadas en forma dicotómica reducían la posibilidad de que los estudiantes respondieran de una manera más cercana a su realidad. Objetivo: obtener las características psicométricas de una versión revisada y modificada del AEQ, adaptado previamente en México. Método: se trabajó con una muestra de 510 estudiantes universitarios, siguiendo las normas para el desarrollo y revisión de estudios instrumentales; mediante el empleo de análisis factorial confirmatorio y el análisis de validez concurrente. Resultados: la versión final del instrumento quedó integrada por 26 reactivos, agrupados en siete factores: desinhibición, confianza en sí mismo, reducción de la tensión, relajación, incremento de la sexualidad, interacción social y cambios psicofisiológicos; con índice general de Confiabilidad de .937. Discusión y conclusiones: posiblemente la revisión conceptual y operacional influyó en el reacomodo y la eliminación de reactivos en comparación con la versión adaptada previamente en nuestro país; sin embargo, los análisis muestran que las expectativas positivas guardan una relación con la frecuencia de consumo excesivo de alcohol. Se obtuvo una versión del AEQ más corta, con validez de contenido, factorial y concurrente, y un índice de confiabilidad aceptable para cada dimensión.